Implementasi Keamanan Jaringan dengan Packet Filtering Berbasis Mikrotik Untuk Internet Positif Di SMKN 1 Praya - Sumardi Jayanto; Ahmad Tantoni; Hasyim Asyari (Jurnal Ranah Publik Indonesia Kontemporer (Rapik), 2021)
SMKN 1 Praya is one of the schools in NTB with national standards. This school has a very broad environment. In addition, this school also has a fairly good internet network. This can be seen by the breadth of the internet network that almost covers the entire school environment. At SMKN 1 Praya the main problem is the use of internet network data by students to be used to play games and social media during study hours so we need a system that is capable of being a protection so that users cannot use the internet to play games and social media during study hours. . Based on this, the study aims to examine the implementation of network security with mikrotic-based packet filtering at SMKN 1 Praya. In general, this study shows the success of blocking several online game applications such as mobile legend, free fire, TOT and social media such as facebook.